Investigating the mediating role of organizational learning in the relationship between knowledge management aspects and organizational performance of sepah bank in Ardabil province - Sahebnazar, Daryoush; Dadfar, Ebrahim (International Journal of Scientific World, 2016)
The organization’s performance is considered as the qualitative and quantitative base of the development of any country. As long as the organizations do not conduct a survey to evaluate their knowledge assets, knowledge and organizational learning which are considered as the necessary parts of any organization, will not improve the performance and organizational development. Accordingly the aim of this study was to investigate the mediating role of organizational learning in the relationship between knowledge management aspects and organizational performance. The population of this study includes employees of Sepah Bank in Ardabil province branches, and sampling was conducted based on Morgan table which its number was equal to 169 and finally 164 questionnaires were analyzed. A questionnaire was used to collect the data and its reliability was investigated and has been approved using Cronbach’s alpha coefficient. The collected data were studied using modeling techniques, structural equation, and bootstrapping. All of the stages were calculated using Stata and Lisrel software. The results showed that knowledge management aspects (knowledge creation, knowledge storage, knowledge sharing and application of knowledge) play a mediating role in the relationship between knowledge management and organizational performance.